Tracing Social Inequality Through Information Proverty: An Analytical Literature Survey and Way Forward - Ghosh, Parna; Barui, Tapan (Access: An International Journal of Nepal Library Association, 2025)
Information poverty is actually “manifested disparity between individuals, communities or nations in mobilizing society’s information resources for the benefit of their lives and development, which may take the form of information divide, knowledge gap etc.” Information poverty is a problem of social inequality. We are moving towards post-truth society, but it is not possible if we eliminate the social stratification among us. The purpose of this article is to explore the existing research in and around the topic & identifying gaps in the literature. This paper presents a literature review on four facets– i) Community Information Service, ii) Community Information Service through public libraries, iii) Information inequality and information poverty and iv) Digital divide and the libraries. From the literature survey information poverty is an important research topic today as society’s progress will depend on the power of information to increase the productivity of the citizen.